ANALISIS IMPLEMENTASI CHECKAND BALANCE SYSTEM DALAM PENGELOLAAN KEUANGAN NEGARA - Rumbia, Moh Firdaus; Junanto, Deny (Badan kebijakan Fiskal, 2009)
Check and balance system is exceptionally relevant in public finance management. It can assure that every institutions—legislative, executive, and auditive—whose involve in public finance management perform appropriately based on its role and function. This paper analyzes and compares the implementation of check and balances system in public finance management in Australia, Philippines and including Indonesia. The findings are employed to develop the system in Indonesia. Once it has been implemented, none of the institutions will abuse their power. Consequently the public budget will be more accountable and transparent for the benefit of the people.